Introduction to the Special Issue: NCAA Division III College Athlete Development and Experience - Bonni Hodges; Lindsey Darvin (Bowling Green State University, 2022)
There is abundant literature on a plethora of topics associated with intercollegiate athletics. Yet, when one begins to dig deeply into the previous literature, it becomes apparent that most of the attention of this work has focused on Division I (DI) of the National Collegiate Athletic Association [NCAA]. To that end, while the NCAA Division III (DIII) level contains a greater number of institutions and more athletes than either of the other divisions of play, this group has largely been ignored throughout the previous literature (NCAA, 2021a; Williams, et al, 2020). This lack of previous literature, combined with the fact that each NCAA division has its own unique characteristics, underscore the need for additional research throughout intercollegiate sport levels of play. We sought to identify and showcase work being done to understand the well-being challenges and initiatives to enhance the Division III athlete's experience.